ANALISIS FAKTOR-FAKTOR PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus pada Pemerintah Kabupaten dan Kota se-Jawa Barat) - Putri Puspita Ayu (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2017)
Abstract: This research was conducted to analyze the factors that influence the Local Government Financial Report, case study at the Government of Regency and City in West Java. This research uses analytical descriptive method. In collecting data conducted, the researchers conducted data collection through field research and library research. The author obtained research data from the Badan Pemeriksa Keuangan (BPK). BPK is a State institution in the Indonesian state administration system which has authority to examine the management, financial responsibility of the State and the Region. Factors disclosure of Local Government Financial Statements proxied by total realization of regional expenditure, total assets, level of dependence, and audit opinion. Where based on statistical results indicates that the total realization of regional expenditure has no influence on full disclosure of Local Government Financial Statements while Total assets, level of dependence, and audit opinion have a significant influence on full disclosure of local government financial statements.Keywords: Dependency Level, Audit Opinion, Disclosure of Government Financial Report